Terapia ocupacional e a abordagem da dimensão espiritual no contexto hospitalar: em busca de um como fazer através da relação entre ocupação e espiritualidade - Pinto, Bruna Teixeira (Universidade Federal de São Carlos, 2024)
The hospital is a place that covers different phases of the human life cycle, from birth, diagnostic discoveries to proximity to finiteness of life, which favors the pursuit of essential meanings to life and the treatment process itself. Research shows that the inclusion of spirituality in the therapeutic processes can improve the patients’ quality of life as well as stimulate either a faster healing process or confrontation with the diseases. Thus, spirituality has been gaining ground in the academic world, being increasingly present in the triad patient-care in health-support team. This study aimed to characterize the actions of occupational therapy with patients with chronic non-communicable diseases and family caregivers, in approaching the spiritual dimension from the perspective of occupation, in the context of hospitalization. This is a descriptive study, with a qualitative approach, carried out with 23 occupational therapists, 9 patients with non-communicable chronic diseases and 16 family caregivers. Data collection was conducted through na online questionnaire and an open interview consisting of guiding questions, which were examined using thematic content analysis. The study shows that spirituality is intrinsic to the experience of patients with chronic illness and their caregivers, present in both home and hospital contexts. It highlights the importance of recognizing and strengthening the spiritual dimension in hospital care as a therapeutic strategy that enhances the effectiveness of care in contexts of illness. When incorporated into occupational therapist’s practice through meaningful activities and humanized, person-centered care, spirituality contributes to coping with illness, strengthening life’s sense of meaning, and promoting well-being, integrating health and occupational performance. The study underscores the need for theoretical, ethical, and educational advances so that spirituality is included in a conscious, respectful, and well-grounded manner within the field of Occupational Therapy.
Occupational therapy and the approach to the spiritual dimension in the hospital context: in search of a how-to through the relationship between occupation and spirituality
Keywords: Espiritualidade; Doenças crônicas; Terapia Ocupacional; Hospital; Spirituality; Chronic diseases; Occupational therapist; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar